Determination of rooftop photovoltaic panel installation potential in public buildings and consideration of architectural design for energy production increase: a case study of Yalova - Arslan, Furkan; Türkdoğan, Sunay (İdris Karagöz, 2022)
Today, the increase in technological and economic developments has increased the living standards and the increase in the population has revealed the need for high energy. Considering that the majority of the energy we need is produced from fossil fuels, it is not possible to meet the increasing energy demand by fossil fuels due to both economically and environmentally because the fossil fuels are running out and harmful to the environment. Therefore, the trend towards cleaner and sustainable energy sources is increasing rapidly. The direct or indirect energy source of all renewable energy sources is the sun, and it has a production potential far above the world's energy needs. Due to its geographical location, our country has a significant potential to benefit from solar energy compared to other countries, and its energy production capacity is large enough to meet all needs. In this study, it has been studied how much of the energy production potential with such a high capacity can be met by solar power plants that can be installed on the roofs of public buildings in Yalova province, and it is shown how architectural plans can be changed to increase the existing potential during the design stage and how much energy production can be increased with architectural optimization. This study will show that solar energy potential has not been taken into account in architectural drawings until now, but with up to 592% increase rates shown in the study from now on, solar architecture should be taken into account in public or private building architecture plans throughout the country from Yalova province and on this occasion how high the amount of energy that can be brought to our country is.

Günümüzde, teknolojik ve ekonomik gelişmelerin artması beraberinde yaşam standartlarını arttırmış ve nüfusun da her geçen gün artmaya devam etmesi yüksek enerji ihtiyacını ortaya çıkarmıştır. İhtiyacımız olan enerjinin büyük kısmının fosil yakıtlardan üretildiği düşünüldüğünde artan enerji talebinin tükenmekte ve çevreye zararlı olan fosil yakıtlarla karşılanması hem ekonomik hem de çevresel açıdan mümkün değildir. Bundan dolayı daha temiz ve tükenmeyen enerji kaynaklarına yönelim hızla artmaktadır. Tüm yenilenebilir enerji kaynaklarının direkt veya dolaylı enerji kaynağı güneş olup dünyanın enerji ihtiyacının çok üzerinde bir üretim potansiyeline sahiptir. Ülkemiz coğrafi konumu itibariyle güneş enerjisinden yararlanma konusunda diğer ülkelere nazaran önemli bir potansiyele sahip olup enerji üretim kapasitesi tüm ihtiyaçları karşılayabilecek büyüklüktedir. Bu çalışmada, bu denli yüksek kapasiteye sahip enerji üretim potansiyelinin Yalova ili genelindeki kamu binalarının çatılarında kurulabilecek güneş enerji santralleri ile ne kadarının karşılanabileceği incelenmiş olup mevcut potansiyelin arttırılması için mimari planların tasarım aşamasında nasıl değiştirilebileceği ve mimari optimizasyon ile enerji üretim miktarlarının ne oranda artabileceği gösterilmiştir. Bu çalışma bugüne kadar mimari çizimlerde güneş enerji potansiyelinin göz önüne alınmadığını ancak bundan sonra, çalışmada gösterilen %592’ye kadar artış oranlarıyla birlikte Yalova ili genelinden tüm ülkedeki kamu veya özel bina mimari çizimlerinde solar enerjisinin dikkate alınması gerektiğini ve bu vesileyle ülkemize kazandırılabilecek enerji miktarının ne kadar yüksek olduğunu gösterecektir.
Kamu binalarında çatı üzeri fotovoltaik panel kurulum potansiyelinin belirlenmesi ve enerji üretim artışı için mimari tasarımın ele alınması: Yalova ili örneği
Keywords: Photovoltaic Power Systems; Fotovoltaik Güç Sistemleri